Appendix A: Natural Numbers and Integers

9/14 problems solved

Exercise A.1

We can see that \(s\) is one-to-one from P2 of the Peano Axioms.

Every element in \(N \setminus \{1\}\) can be expressed as \(a + s(b)\). From Theorem 1, there is \(s(a + b)\) that equals this element so \(s\) is onto.

Therefore, \(s\) is a bijection.

This can be done over and over with no end and the resulting set can still have a bijection to a smaller one. Therefore, the set \(N\) must be an infinite collection of elements.

Exercise A.2

From P1 of the Peano Axioms, we know that \(s(1) \neq 1\). Given that \(s(a) \neq a\), then \(s(s(a)) \neq s(a)\) from P2 of the Peano Axioms.

Exercise A.3

Given \(a \in N\), define \(M = \{b \in N : a + b \neq b\}\). We can see that \(1 \in M\) since \(a + 1 \neq 1\). Moreover, if \(c \in M\) then \(s(c)\) must also be in \(M\) since \(a + c \neq c\) implies \(s(a + c) \neq s(c)\) and finally \(a + s(c) \neq s(c)\).

From the Axiom of Induction, \(M = N\) so \(a + b \neq b\) for all \(a, b \in N\).

Exercise A.4

(a) Suppose there are two different least elements \(a, b \in N\). By definition, \(a \leq b\) and \(b \leq a\). It is not possible for either \(a < b\) or \(b < a\) without contradicting prior definitions. Therefore, \(a = b\).

(b) If there was an element \(a \in N\) that was not 1 that was the least element of \(N\), then there exists \(n\) such that \(1 = a + n\). However, from P1 of the Peano Axioms, \(s(a) \neq 1\) for all \(a\). This is a contradiction so 1 must be the least element of \(N\).

Suppose there was a greatest element of \(N\) called \(a\). This element is greater than or equal to all other elements in \(N\). However, \(s(a) > a\) which is a contradiction. Therefore, there is no greatest element of \(N\).

Exercise A.5

We know that \((m', n') \sim (m, n)\) and \((p', q') \sim (p, q)\). By definition, this means \(m' + n = n' + m\) and \(p' + q = q' + p\).

For the equality to hold, this requires \((m' + p', n' + q') \sim (m + p, n + q)\). In turn, this means \((m' + p') + (n + q) = (n' + q') + (m + p)\). Using the equalities above, this is true.

Exercise A.6

\[ \begin{align} [m', n'] \cdot [p', q'] &= [m, n] \cdot [p, q] \\ [m' q' + n' p', n' q' + m' p'] &= [m q + n p, n q + m p] \\ \end{align} \]

To prove the above equality, we want to show that \[(m' q' + n' p') + (n q + m p) = (n' q' + m' p') + (m q + n p)\]

Since \((m', n') \sim (m, n)\) and \((p', q') \sim (p, q)\), this means \(m' + n = n' + m\) and \(p' + q = q' + p\).

Exercise A.7

There must be a zero element due to condition R3. To show the zero element is unique, assume there are two zero elements, \(0\) and \(0'\), for the sake of contradiction. By R1, \(0 + 0' = 0' + 0\). Since both are zero elements, this simplifies to \(0 = 0'\). Therefore, the zero element is unique.

Exercise A.8

There must exist a unique additive inverse \(-a\) due to R3. To show this additive inverse is unique, assume there are two additive inverses, \(-a\) and \(-a'\), for the element \(a\). From R2, \(-a + (a + -a') = (-a + a) + -a'\). Since they are additive inverses, ths simplifies to \(-a = -a'\). Therefore, the additive inverse is unique.

Exercise A.9

(a) \(R = \{0\}\)

By exhaustion, we can see that for all elements in \(\{0\}\),

\[ 0 + 0 = 0 + 0 \\ 0 + (0 + 0) = (0 + 0) + 0 \\ \text{There is } 0 \in R \text{ such that } 0 + 0 = 0 \\ 0 \cdot (0 \cdot 0) = (0 \cdot 0) \cdot 0 \\ 0 \cdot (0 + 0) = 0 \cdot 0 + 0 \cdot 0 \text{ and } (0 + 0) \cdot 0 = 0 \cdot 0 + 0 \cdot 0 \]

All of these expressions evaluate to 0.

(b) \(R = \mathbb{Z}_2\)

Proving R1: When \(a = b\), this is proven by reflexivity. For \(0 + 1 = 1 + 0\), both sides evaluate to \(1\).

Proving R2: When \(a = 0\), both sides simplify to \(b + c = b + c\) which is true by reflexivity. Looking at the case where \(a = 1\), when \(b = 0\) both sides simplify to \(1 + c = 1 + c\) which is true by reflexivity. Now when \(a = b = 1\), we can look at both cases where \(c = 0\) and \(c = 1\) and see the equality holds and is equal to \(0\) and \(1\) respectively.

Proving R3: When \(a = 0\), then \(x = 0\) for \(b = 0\) or \(x = 1\) for \(b = 1\). When \(a = 1\), then \(x = 1\) for \(b = 0\) or \(x = 0\) for \(b = 1\).

Proving R4: When \(a = 0\) or \(b = 0\) or \(c = 0\), the product is \(0\) on both sides. When \(a = b = c = 1\), then both sides evaluate to \(1\).

Proving R5: For \(a \cdot (b + c)\), when \(a = 0\) this is true since \(0\) or \(1\) times \(0\) is \(0\). When \(a = 1\), then the equality evaluates to \(b + c = b + c\) which is trivially true by reflexivity.

(c) \(R = 2\mathbb{Z}\)

Since addition and multiplication are taken from \(\mathbb{Z}\), R1, R2, R4, and R5 are all still true. To show R3 is true, we must show \(x \in 2\mathbb{Z}\). Fix \(a = 2m\) and \(b = 2n\). Solving for \(x\), we find \(x = 2n - 2m = 2(n - m)\). Therefore, \(x \in 2\mathbb{Z}\).

(d) \(R = 2^X\)

Proving R1:

\(A \bigtriangleup B = (A \setminus B) \cup (B \setminus A) = (B \setminus A) \cup (A \setminus B) = B \bigtriangleup A\)

Proving R2:

\(A \bigtriangleup (B \bigtriangleup C) = A \bigtriangleup ((B \setminus C) \cup (C \setminus B)) = (A \setminus ((B \setminus C) \cup (C \setminus B))) \cup (((B \setminus C) \cup (C \setminus B)) \setminus A) \)

(e) \(R = \langle F, +, \cdot \rangle\)

Exercise A.10

From Theorem 18, every element has a unique additive inverse. Therefore, if we add the additive inverse of \(c\), \(-c\), to both sides of \(a + c = b + c\), then these cancel to leave us with \(a + b\).

Exercise A.11

For the sake of contradiction, let's assume there are two identity elements of a ring, \(1\) and \(1'\). This means that \(1 \cdot 1' = 1\). However, since this is the identity element, it also means that \(1 \cdot 1' = 1' \cdot 1 = 1'\). Therefore, \(1 = 1'\).

Exercise A.12

Exercise A.13

Exercise A.14